Using network science to map what Montréal bilinguals talk about across languages and communicative contexts - Tiv, Mehrgol; Gullifer, Jason W.; Feng, Ruo Ying; Titone, Debra (Journal of neurolinguistics, 2020)
Recent work within the language sciences, particularly bilingualism, has sought new methods to evaluate and characterize how people differentially use language across different communicative contexts. These differences have thus far been linked to changes in cognitive control strategy, reading behavior, and brain organization. Here, we approach this issue using a novel application of Network Science to map the conversational topics that Montréal bilinguals discuss across communicative contexts (e.g., work, home, family, school, social), in their dominant vs. non-dominant language. Our results demonstrate that all communicative contexts display a unique pattern in which conversational topics are discussed, but only a few communicative contexts (work and social) display a unique pattern of how many languages are used to discuss particular topics. We also demonstrate that the dominant language has greater network size, strength, and density than the non-dominant language, suggesting that more topics are used in a wider variety of contexts in this language. Lastly, using community detection to thematically group the topics in each language, we find evidence of greater specificity in the non-dominant language than the dominant language. We contend that Network Science is a valuable tool for representing complex information, such as individual differences in bilingual language use, in a rich and granular manner, that may be used to better understand brain and behavior. [Display omitted] •Quantifying individual differences in bilingual social language use is important.•We propose a novel application of Network Science to map what bilinguals talk about.•We find that bilinguals talk about different topics in each of their daily contexts.•Bilinguals talk about more topics across more contexts in their dominant language.•There is greater topic specificity in the non-dominant language.